Neuroevolution and neurodegeneration: Two sides of the same coin? - Foster, Jonathan; Boord, P.; Smith, M. (Cambridge University Press, 2012)
This chapter will consider whether neurodegenerative diseases may be informative with respect to the scaling up of the central nervous system (CNS) over evolutionary time. Neurodegenerative illnesses are becoming increasingly prominent as the world's population ages demographically. Alzheimer's disease (AD) represents the most common form of dementia, a major neurodegenerative illness. AD brain pathology progresses in a well-characterised dynamic sequence: there is an advancing wave of cortical atrophy sweeping from limbic and temporal cortices into association areas of the cortex which subserve higher order aspects of cognition, including declarative memory (Braak and Braak, 1995). In contrast, neuropathological changes are minimal in brain regions which mediate more fundamental cognitive processes underlying perception and movement. Taken together, are these changes informative with respect to how the brain evolved? Specifically, does the sequence of neuropathology and cognitive symptomatology in AD represent a type of ‘reverse ontogeny’ in humans? Additionally, in the context of pragmatic evolutionary considerations, could a better evolutionary understanding of the brain help in improved diagnosis and/or treatment for neurodegenerative illnesses such as AD?